Metalliferous mine dust: human health impacts and the potential determinants of disease in mining communities - Entwistle, Jane A.; Hursthouse, Andrew S.; Marinho Reis, A. Paula; Stewart, Alex G. (Current pollution reports, 2019)
Purpose of Review: Many factors influence the health impact of exposure to metalliferous mine dusts and whilst the underpinning toxicology is pivotal, it is not the only driver of health outcomes following exposure. The purpose of this review is twofold: (i) to highlight recent advances in our understanding of the hazard posed by metalliferous mine dust and (ii) to broaden an often narrowly framed health risk perspective to consider the wider aetiology of the potential determinants of disease. Recent Findings: The hazard posed by metalliferous dusts depends not only on their abundance and particle size but other properties such as chemical composition, solubility, shape, and surface area, which all play a role in the associated health effects. A better understanding of the mechanisms that lead to toxicity, such as recent advances in our understanding of the role played by reactive oxygen species (ROS), can help in the development of improved in vitro models to support risk assessments, whilst biomonitoring studies have the potential to guide risk management decisions for mining communities. Summary: Environmental exposures are complex; complex geochemically and complex geographically. Research linking the environment to human health is starting to mature, highlighting the subtlety of multiple exposures, mixtures of substances, and the cumulative legacy effects of life in disrupted and stressed environments. We are evolving more refined biomarkers to identify these responses, which enhances our appreciation of the burden of effects on society and also directs us to more sophisticated risk assessment approaches to adequately address evolving regulatory and societal needs.